2021
DOI: 10.3390/pathogens10040416
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Strain Distribution before and after Introducing Rotavirus Vaccine in India

Abstract: In April 2016, an indigenous monovalent rotavirus vaccine (Rotavac) was introduced to the National Immunization Program in India. Hospital-based surveillance for acute gastroenteritis was conducted in five sentinel sites from 2012 to 2020 to monitor the vaccine impact on various genotypes and the reduction in rotavirus positivity at each site. Stool samples collected from children under 5 years of age hospitalized with diarrhea were tested for group A rotavirus using a commercial enzyme immunoassay, and rotavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
18
3
Order By: Relevance
“…These results in our MSD cases are similar to those previously found in hospital-based studies in Mozambique, which also reported G3P [8] as the most frequent combination in MSD [18]. In addition, G3P [8] was also recorded as the most frequent combination in the post-vaccine introduction in other countries such as Fiji and India [37,38]. The dynamic change in the diversity of rotavirus genotypes, we observed in the post-vaccine introduction period in our study, may not explain whether this change is related to vaccine introduction in Mozambique, because genotypes shifting may occur in countries regardless of the implementation or not of vaccine into immunization programs, demonstrating a fluctuation of genotypes within and between countries [39].…”
Section: Discussionsupporting
confidence: 91%
“…These results in our MSD cases are similar to those previously found in hospital-based studies in Mozambique, which also reported G3P [8] as the most frequent combination in MSD [18]. In addition, G3P [8] was also recorded as the most frequent combination in the post-vaccine introduction in other countries such as Fiji and India [37,38]. The dynamic change in the diversity of rotavirus genotypes, we observed in the post-vaccine introduction period in our study, may not explain whether this change is related to vaccine introduction in Mozambique, because genotypes shifting may occur in countries regardless of the implementation or not of vaccine into immunization programs, demonstrating a fluctuation of genotypes within and between countries [39].…”
Section: Discussionsupporting
confidence: 91%
“…G1P [8] was the predominant genotyped reported in the pre-vaccination period, whereas G3P [8] became the dominant genotype in the post-vaccination period. Geographic variation in genotype distribution was noted between northern and southern sites [33].…”
mentioning
confidence: 96%
“…Castells et al reported detection of rotavirus in calves reared for beef and dairy production in Uruguay [24]. Multiple genotypes associated with bovine disease were detected including G6P [11] (40.4%), G6P [5] (38.6%), G10P [11] (19.3%), as well as the uncommon genotype G24P [33] (1.8%) [24].…”
mentioning
confidence: 99%
“…Long-term surveillance pre- and post-vaccine introduction was also conducted at five sentinel sites in India between 2012 to 2020 by Varghese and colleagues [ 33 ]. The Rotavac vaccine was introduced in 2016 resulting in a decrease in rotavirus-associated hospitalisations.…”
mentioning
confidence: 99%
“…G1P[8] was the predominant genotyped reported in the pre-vaccination period, whereas G3P[8] became the dominant genotype in the post-vaccination period. Geographic variation in genotype distribution was noted between northern and southern sites [ 33 ].…”
mentioning
confidence: 99%